Social Criticism in the Drama "Maling" and "Eksekusi" by Ilham Zoebazary - Hana Mumtazia Nurhaq; Rudi Adi Nugroho (Jurnal Sastra Indonesia, 2024)
Literary works are often considered separate from the life of society. Literary works can reflect the life of society in a certain period and respond to the life that occurred when the literary work was created. This research describes the social criticism in the Drama Manuscripts titled "Maling" and "Eksekusi" in the Collection of the Drama Manuscripts titled Gandrung by Ilham Zoebazary. The social criticism in these manuscripts is analyzed using a Sociology of Literature approach. The research method used is a qualitative descriptive method. The data collection techniques used in this research were library study and note-taking. The data was then analyzed using three stages proposed by Miles & Huberman (1994), namely 1) data reduction, 2) data display, and 3) conclusion drawing. The research results show that the two texts analyzed contain five types of social criticism: criticism of legal, economic, violent, political, and gender issues. These criticisms relate to the situation when these texts were born and the current situation. The various problems the author presents through the texts can make the reader reflect on the events and use them as valuable lessons for facing life today.